2019
DOI: 10.1016/j.celrep.2019.03.108
|View full text |Cite
|
Sign up to set email alerts
|

PAD2-Mediated Citrullination Contributes to Efficient Oligodendrocyte Differentiation and Myelination

Abstract: Summary Citrullination, the deimination of peptidylarginine residues into peptidylcitrulline, has been implicated in the etiology of several diseases. In multiple sclerosis, citrullination is thought to be a major driver of pathology through hypercitrullination and destabilization of myelin. As such, inhibition of citrullination has been suggested as a therapeutic strategy for MS. Here, in contrast, we show that citrullination by peptidylarginine deiminase 2 (PAD2) contributes to normal oligodendroc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 63 publications
5
76
0
Order By: Relevance
“…The most prominent functions of OLs is forming the myelin sheath, which is essential for proper neuronal communication and central nervous system function [76]. Notably, PADI2 levels increased during OLs differentiation, and PADI2 acts as a chromatin modifier to promotes oligodendrocyte precursor cell differentiation [77]. Therefore, PADI2 contributes to efficient myelination and motor and cognitive functions.…”
Section: Padi2 Shows Specific Substrate Preferencesmentioning
confidence: 99%
“…The most prominent functions of OLs is forming the myelin sheath, which is essential for proper neuronal communication and central nervous system function [76]. Notably, PADI2 levels increased during OLs differentiation, and PADI2 acts as a chromatin modifier to promotes oligodendrocyte precursor cell differentiation [77]. Therefore, PADI2 contributes to efficient myelination and motor and cognitive functions.…”
Section: Padi2 Shows Specific Substrate Preferencesmentioning
confidence: 99%
“…PADs have received particular attention due to roles in cancer (20,22,26,27), rheumatoid arthritis (28)(29)(30)(31)(32)(33), multiple sclerosis (34)(35)(36)(37)(38), as well as due to their contribution to skin physiology and diseases (39). PADs have furthermore been shown to play crucial roles in hypoxia and CNS regeneration (40)(41)(42)(43)(44), and roles for PAD2 in promotion of oligodendrocyte differentiation and myelination have been shown (45). PAD-mediated mechanisms have also been related to aging (46,47).…”
Section: Introductionmentioning
confidence: 99%
“…Via these alterations PADIs regulate fundamental physiological and cellular processes. The bestestablished role of citrullination is in innate immunity, through mediating the release of neutrophil extracellular traps (NETs) 12 but a plethora of studies have shown that PADIs also regulate gene expression, chromatin compaction, nerve myelination, skin homeostasis and the establishment of ground state pluripotency 8,13,14 . Notably, deregulation of PADIs is strongly implicated in the aetiology of a host of pathologies including autoimmunity (rheumatoid arthritis, ulcerative colitis, psoriasis and type I diabetes), neurodegeneration (multiple sclerosis, Alzheimer's and prion diseases) and metastatic cancer 13,[15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental in vivo models of PADI over-expression show that deregulation of citrullination drives the development of multiple sclerosis and cancer 16,20 , while genetic ablation or chemical inhibition of different PADI family members has been shown to mitigate against some the pathologies mentioned above 16,[21][22][23] . Although the underlying mechanism in the above cases is aberrantly high citrullination, loss of PADI activity is also deleterious and has been shown to compromise neurodevelopment, fertility and embryo development 8,14,24 . PADIs have therefore emerged as important therapeutic targets 25 and this has motivated the study of their exquisite regulation by calcium and the physiologically relevant mechanisms of their activation [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%